Catalytic Reaction Rates Controlled by Metal Oxidation State: C−H Bond Cleavage in Methane over Nickel‐Based Catalysts. Issue 13 (27th February 2017) - Che, Fanglin; Ha, Su; McEwen, Jean‐Sabin
Abstract: The role of low concentrations of carbon complexes in hydrocarbon decomposition over transition metal surfaces has been a topic of much debate over the past decades. It is also a mystery as to whether or not electric fields can enhance hydrocarbon conversion in an electrochemical device at lower than normal reforming temperatures. To provide a "bottom‐up" fundamental insight, C−H bond cleavage in methane over Ni‐based catalysts was investigated. Our theoretical results show that the presence of carbon or carbide‐like species at the interface between the Ni cluster and its metal‐oxide support, as well as the application of an external positive electric field, can significantly increase the Ni oxidation state. Furthermore, the first C−H bond cleavage in methane is favored as the local oxidation state of Ni increases. Thus, the presence of a low concentration of carbon species, or the addition of a positive electric field will improve the hydrocarbon activation process. Abstract : A bottom‐up fundamental study demonstrates that the catalytic activity of the first C−H bond cleavage in methane is controlled by the local oxidation state of nickel. Increasing positive field strength (A) or inclusion of low concentrations of interfacial carbon species (B) leads to a partial positive charge in the nickel cluster, which can accelerate C−H cleavage.